Re-emergence of Asia in the New Industrial Era - Tiwari, Siddhartha Paul (Technium Social Sciences Journal, 2022)
The dawn of the new industrial era (Fourth Industrial Revolution or 4 IR, Industry 4.0, “McLuhan” stage) characterised by IT-based modern technologies and global value chains has regained the Asian economic strength. Overarching impact of 4 IR is expected on the physical, digital and biological world. Several Asian countries have maintained high growth and have displayed true globalization by possessing elements and desiderata of the 4 IR. Asia has also displayed its innovative strength in many determinants of 4 IR. Although a gradual transition from labour to capital to talent is slated to happen, Asia will have its own amalgam of the three case-by-case. For example, some Asian countries have demographic assets to use labour in low-skill jobs and they will continue to compete as low-cost manufacturing hubs for a substantially long period despite high proportion of ageing people and less birth rate. Human talent-intensive services like healthcare and education stand to benefit from 4 IR by way of cost-reduction but concerted efforts of public and private sectors are needed in these areas. Unemployment and inequality may rise initially but may be offset to a sizeable extent by new jobs and engagements and also by reorientation of knowledge, skill and attitude, the three realms of education, through continuous training, skill upgradation and self-renewal. There could be eugenic effects such as defect-rectification at early developmental stages and ultimately moving towards designer human beings in the long long run. Significant role of the state, policy and mode of governance was observed in bringing about the 4 IR. It is hoped that while thriving on the fruits of 4 IR, all stakeholders would also unite for maintaining a vigil and holding up the human values like conscience, creativity and empathy to mar the possible ill-effects of the 4IR that could be dreaded in its most dehumanized form in the long run.